PENGUATAN USAHA MIKRO KECIL DAN MENENGAH DI DESA JEMEKAN KECAMATAN RINGINREJO KABUPATEN KEDIRI - Lilik Susanti; Zaidatul Inayah; Ni'matullah Al-Jauhariyah; Moh. Irmawan Jauhari (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2022)
This activity is aimed at developing the sense of sensitivity and social cognition of students as well as assisting the development process. Asset-Based Community Development (ABCD) is considered the right approach to the above problem. This is because ABCD is an approach in community development that is in a large stream of seeking to realize an order of social life in which the community is the actor and determinant of development efforts in their environment or what is often referred to as Community-Driven Development (CDD). The result activity is, strengthening UMKM in Jemekan Village with the Bu Istiqomah bitter melon chip pilot project resulted in three main points so that UMKM become strong and empowered. First, you have to be willing to master technology, considering that the restrictions on community activities can only be overcome with technology. Second, improving the quality of UMKM human resources which will lead to UMKM creativity and productivity. Third, networking or collaboration as a form of cooperation and building a better system for UMKM actors.